2001
DOI: 10.1080/00913367.2001.10673641
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Based Measures for Assessing Advertising Effects: A Comparison of Explicit and Implicit Memory Effects

Abstract: Prior marketing studies investigating memory for advertisements have relied almost exclusively on examining effects contingent on explicit memory retrieval. This process involves a deliberate effort on the part of the consumer to think back to an advertisement in an attempt to recall the ad information. Studies in this area have shown that a lengthy delay between ad exposure and test, as well as divided attention during the ad exposure episode, hinder or even eliminate successful explicit memory retrieval. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
133
1
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 31 publications
7
133
1
9
Order By: Relevance
“…The disassociation between implicit and explicit memory has been suggested by numerous scholars (Graf andSchacter 1985, 1987;Jacoby and Dallas 1981;RichardsonKlavehn and Bjork 1988;Roediger 1990;Schacter 1987;Tulving, Schacter, and Stark 1982). Indeed, in a recent study on implicit and explicit memory for brands placed in movies, there was no relationship between implicit and explicit memory (Yang 2004; see also Auty and Lewis 2004;Shapiro and Krishnan 2001).…”
Section: In-game Advertising: Implicit Versus Explicit Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…The disassociation between implicit and explicit memory has been suggested by numerous scholars (Graf andSchacter 1985, 1987;Jacoby and Dallas 1981;RichardsonKlavehn and Bjork 1988;Roediger 1990;Schacter 1987;Tulving, Schacter, and Stark 1982). Indeed, in a recent study on implicit and explicit memory for brands placed in movies, there was no relationship between implicit and explicit memory (Yang 2004; see also Auty and Lewis 2004;Shapiro and Krishnan 2001).…”
Section: In-game Advertising: Implicit Versus Explicit Memorymentioning
confidence: 99%
“…Indeed, unlike the generally passive audiences of most television shows or movies, video game players are more active, and their attention is divided between what they are watching and the game controls (see, e.g., Grodal 2000), which may interfere with memory for the in-game brand placements (Liu andShrum 2002, 2005). For example, Shapiro and Krishnan (2001) found that when people's attention was divided between visually presented advertisements and listening to a broadcast, their memory for the advertisements was diminished. Nevertheless, it is not yet clear how the interactivity of video games might influence the effect of brand placements on memory.…”
Section: In-game Advertising Versus Brand Placements In Television Prmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the effects of endorser characteristics, extant endorsement research has also verified the perceiver effects of selfconstruals [35][36][37][38], self-regulatory [39], self-concept [40], implicit selftheory [41], self-empowerment [42], and explicit and implicit memory [43].…”
Section: The Impacts Of Perceiver Characteristics On Brand Evaluationsmentioning
confidence: 99%
“…Since individuals' attitudes toward those elements could influence their future behaviors regarding a brand and=or product, researchers and ad agency professionals have attempted to acquire satisfactory answers regarding related questions (Shapiro, MacInnis, & Heckler, 1997). Regarding the likeability of an ad and the advertised brand and product, many different factors have been investigated as essential, including types of media (Yang & Smith, 2009), uniqueness of the vehicle (Zhu & Meyers-Levy, 2005), length of commercials (Spence & Driver, 1998), advertising appeal (Shapiro & Krishnan, 2001), product characteristics (El-Murad & West, 2004), and brand awareness (Vanden Bergh & Stuhlfaut, 2006). In addition, the creativeness of an ad (Sasser & Koslow, 2008) and the roles of audience members as advertising professionals or regular consumers (Chong, 2006) were discussed as important factors in predicting individuals' attitudes toward an ad, a brand, and the product appearing in the ad.…”
Section: Sogang University South Koreamentioning
confidence: 99%